Factors influencing stomatal conductance in response to water availability in grapevine: a meta‐analysis. Issue 4 (12th January 2017) - Lavoie‐Lamoureux, Anouk; Sacco, Dario; Risse, Paul‐André; Lovisolo, Claudio
Abstract : The main factors regulating grapevine response to decreasing water availability were assessed under statistical support using published data related to leaf water relations in an extensive range of scion and rootstock genotypes. Matching leaf water potential (Ψleaf ) and stomatal conductance (gs ) data were collected from peer‐reviewed literature with associated information. The resulting database contained 718 data points from 26 different Vitis vinifera varieties investigated as scions, 15 non‐ V. vinifera rootstock genotypes and 11 own‐rooted V. vinifera varieties. Linearised data were analysed using the univariate general linear model (GLM) with factorial design including biological (scion and rootstock genotypes), methodological and environmental (soil) fixed factors. The first GLM performed on the whole database explained 82.4% of the variability in data distribution having the rootstock genotype the greatest contribution to variability (19.1%) followed by the scion genotype (16.2%). A classification of scions and rootstocks according to their mean predicted gs in response to moderate water stress was generated. This model also revealed that gs data obtained using a porometer were in average 2.1 times higher than using an infra‐red gas analyser. The effect of soil water‐holding properties was evaluated in a second analysis on a restricted database and showed a scion‐dependant effect, which was dominant over rootstock effect, in predicting gs values. Overall the results suggest that a continuum exists in the range of stomatal sensitivities to water stress in V. vinifera, rather than an isohydric–anisohydric dichotomy, that is further enriched by the diversity of scion‐rootstock combinations and their interaction with different soils.